SILICA GEL MODIFIED WITH FUNCTIONALIZED CALIXARENES. PREPARATION AND CHARACTERIZATION - RANETE, Raul; PETRAR, Petronela M.; ȘEPTELEAN, Raluca; PERHAIŢĂ, Ioana; NEMES, Gabriela (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This work presents the synthesis and characterization of novel products obtained by the chemical bonding of lower rim substituted calix[4]- and calix[8]arene macrocycles to silica gel surfaces modified with aminopropyl chains. The products were investigated by thermogravimetric analysis (DTG, EGA), surface area analysis (BET), as well as by electron microscopy (TEM, SEM).